PERSPEKTIF HUKUM PERKAWINAN ANTAR AGAMA YANG BERKEADILAN DIKAITKAN DENGAN POLITIK HUKUM PERKAWINAN INDONESIA DALAM RANGKA PEMBANGUNAN HUKUM KELUARGA NASIONAL - Tengku Erwinsyahbana (Indonesian Journal of Dialectics, 2012)
It is likely that inter-religion marriage often takes place due to plurality adhered by the Indonesian people. Many couples have not had their inter-religion marriage registered due to refusal by the Civil Registry Office to register their marriage on grounds that the inter-religion marriage is not permitted in religious teachings, and further, it is not regulated in Law No. 1 of 1974. This fact obviously raised the feeling of injustice and legal uncertainty in the inter-religion marriage so that it is interesting to investigate the aims of which were: to discover the law on inter-religion marriage in the politics on marriage law based on Five Basics Principles of the Republic of Indonesia (Pancasila) when associated with function of the marriage registry institution, to discover the legal certainty of the interreligion marriage conducted overseas when associated with function of the marriage registry under the Indonesian legal system, as well as the inter-religion marriage law in the political perspective on equitable marriage law based on Pancasila as an effort for legal system development of national family. Toanalyzethe research findings, the following theories are adopted, which are, the Pancasila-based legal state, Pancasila-based justice as well as legal development and legal certainty theories.The research was a legal research natured by adopting approaches on legal history and comparative as well as laws and regulations. The research was descriptive nature and in view of the costruction, it was a prescriptive research.The main data required for the research consisted secondary and primary data.Data collection that have been adopted was document study and interview methods The analysis of the data collecting was conducted on a qualitative juridical method focusing on the analysis on the legal certainty and legal aspect which live and grow among the public, as well as legal synchronization.The research indicated that the inter-religionmarriage in Indonesia has taken place due to a legal uncertainty in the context of Law No. 1 of 1974 which did not regulate whether or not the inter-religion marriage practice was permitted. On the contrary, however, the relevant law has opened the possibility of such marriage to took place. It was also possible that the uncertainty on the inter-religion marriage was due to the provisions regarding marriage as set forth in Law No. 1 of 1974 and Law No. 23 of 2006 which conflict with each other. The state should therefore guarantee that the public legal certainty is to be realized as one characteristic indicated in a Pancasila-based legal state is the existence of legal certainty. Viewed from the theories on Pancasila-based justice as well as legal development and legal certainty approache.Thus, to realize public orderliness and harmony, it shall be necessary to only register the marriage at one institution. This has to be conducted as an effort to keep orderliness of population administration and legal certainty when it comes to inter-religion marriage.